Posted by **John** on Wednesday, March 7, 2012 at 9:21pm.

Given the following hypothetical equations,

2A + B → 3C + 2D ΔH = -46.7kJ

C → B ΔH = 13.1kJ

2E → B ΔH = 84.5kJ,

what is the enthalpy change (kJ) for the following reaction?

A → D + 2E

- Chemistry -
**DrBob222**, Wednesday, March 7, 2012 at 9:45pm
Add eqn 1 as is to 3x eqn 2 to 2x the reverse of eqn 3. That will give you 2x the equn you want so take 1/2 of the final equation. When reversing an equation, change the sign of dH. When multiplying an equation, multiply dH by the same number. Add all of them take 1/2 final equation and 1/2 final dH.

## Answer this Question

## Related Questions

- chemistry - Calculate the enthalpy change, ΔrH, for the following reaction...
- Chemistry - Calculate the enthalpy change, ΔrH, for the following reaction...
- Chemistry - Calculate the enthalpy change for the reactions NO(g) + O(g) →...
- Chemistry - Please help me! I don't know how to do this at all. Calculate the ...
- Chemistry - Enthalpy Change Given the following reactions: S(s) + O2(g) → ...
- chemistry - Given the following reactions Fe2O3(s) + 3CO (s) → 2Fe (s) + ...
- Chem - Set up a Hess’s law cycle, and use the following information to calculate...
- Chemistry - ou are given the following data. S(s) + 3/2 O2(g) → SO3(g) &#...
- Chemistry - Can you check my calculations, please? It's for a lab we did in ...
- Chemistry - What is the enthalpy change for the first reaction? Fe2O3(s) →...